Baseline plasma cholinesterase activities in argentine saddle horses from sabana de bogotá (2012)
The determination of cholinesterase (ChE) activity in domestic animals is of great importance for diagnosis and research purposes. The present work was aimed to determine the baseline plasma ChE activities (acetylcholinesterase, AChE and butyrylcholinestarase, BChE) of Argentine saddle horses sampled from equine farms of Bogota (Colombia) and its surroundings. Plasma AChE and BChE catalytic activities were measured in 60 healthy horses by spectrophotometry within the visible spectrum (405 nm). AChE mean ± SD values (nmols/ml/min) for males (n=32) were 1566 ± 301. Age intervals results were, 0.5–5 years: 1526 ± 295, 6–10 years: 1532 ± 313, 11-15 years: 1615 ± 279, and and gt; 15 years: 1617 ± 335. As for females (n=28), mean AChE was 1323 ± 432, with age intervals as follows, 0.5-5 years: 719 ± 108, 6–10 years: 1603 ± 313, 11–15 years: 1225 ± 294, and gt; 15 years: 1519 ± 369. BChE in males were 3304 ± 822; with age intervals, 0.5-5 years: 3383 ± 715, 6–10 years: 3360 ± 766, 11-15 years: 3267 ± 1064, and gt; 15 years: 3206 ± 861. As for females, BChE values were 3097 ± 432, with age intervals: 0.5-5 years: 2467 ± 981, 6–10 years: 3668 ± 750, 11-15 years: 3238 ± 979, and and gt; 15 years: 3015 ± 925. AChE was significantly different between males and females (t test, p and lt; 0.05) and for both genders when age groups were compared (ANOVA, p and lt; 0.05). BChE had higher values than AChE for both genders and yet no significant difference was found when genders were compared. No differences were found in BChE for age groups in both genders. In a second test, 15 random samples, kept at 4 oC for 72 hours, were analyzed for variations when measured every 24h. Neither AChE nor BChE had significant variations in these 24h-apart measurements. The present investigation found baseline activities for the two types of plasma cholinesterases in Argentinian saddle horses. This will allow researchers and clinicians to count on reference values for diagnosis and comparative purposes.